1997
DOI: 10.1136/jnnp.63.6.749
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological assessment of the lesions of significance in vascular dementia

Abstract: Objectives-To better define the neuropathology of vascular dementia. Methods-The neuropathological findings in 18 elderly, undemented subjects free of cerebrovascular disease were compared with 19 elderly undemented subjects who had cerebrovascular disease (many of whom had had a "stroke") and 24 elderly demented subjects who had cerebrovascular disease, but no other pathology to account for dementia. Cases in all groups were selected for absence or no more than very mild Alzheimer type pathology. Results-Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
235
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(245 citation statements)
references
References 21 publications
9
235
0
1
Order By: Relevance
“…Although some studies point to a possible causal relationship with dementia [30][31][32][33], others challenge this point of view [34]. Shrinkage and atrophy of the brain are generally considered to be a risk factor for cognitive decline [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies point to a possible causal relationship with dementia [30][31][32][33], others challenge this point of view [34]. Shrinkage and atrophy of the brain are generally considered to be a risk factor for cognitive decline [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Six studies reported on a combination of people with and without dementia described as a single group. Two studies assessed patients with stroke (Esiri et al, 1997;Santos et al, 2009), one study elderly without describing their cognitive status (Longstreth et al, 2009). Three papers concerned patients with cerebral amyloid angiopathy (CAA) (Olichney et al, 1997;Soontornniyomkij et al, 2010;De Reuck et al, 2011a).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Thirteen studies (41%) diagnosed the patients primarily on neuropathological criteria (Esiri et al, 1997;Olichney et al, 1997;Suter et al, 2002;Rossi et al, 2004;Del Ser et al, 2005;Yip et al, 2005;Haglund et al, 2006;Isojima et al, 2006;Kö vari et al, 2007;Longstreth et al, 2009;Okamoto et al, 2009;De Reuck et al, 2011a, b). The most commonly used neuropathological criteria for AD were the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) (Mirra et al, 1991) and the Braak criteria (Braak and Braak, 1991).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such lesions are a common finding at autopsy in older individuals 2. They are typically considered to measure less than 1 mm in maximum diameter, although no consensus definition exists, and are frequently much smaller.…”
Section: Introductionmentioning
confidence: 99%